2020
DOI: 10.3389/fphys.2020.00770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise-Related Factors on the Perception of Time

Abstract: The concept of time whether considered through the lenses of physics or physiology is a relative measure. Alterations in time perception can have serious implications in sport, fitness and work. Accurate perception of time is an important skill with many time constrained sports (i.e., basketball, North American football, tennis, gymnastics, figure skating, ice hockey, and others), and work environments (i.e., workers who need to synchronize their actions such as police and military). In addition, time distorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
3
19
1
Order By: Relevance
“…The data gathered in Argentina shows that the perception of a faster passage of the week was associated with greater levels of physical activity. This relationship is consistent with previous research showing that a goal-oriented activity is related to the acceleration of passage of time [ 45 ]. As there were no restrictions on physical activity in Argentina at the time of study but there were significant restrictions on exercise opportunities in the UK, France and Italy, the lack of opportunity for exercise in Europe may have prevented variability in exercise activity from significantly affecting the passage of time.…”
Section: Discussionsupporting
confidence: 93%
“…The data gathered in Argentina shows that the perception of a faster passage of the week was associated with greater levels of physical activity. This relationship is consistent with previous research showing that a goal-oriented activity is related to the acceleration of passage of time [ 45 ]. As there were no restrictions on physical activity in Argentina at the time of study but there were significant restrictions on exercise opportunities in the UK, France and Italy, the lack of opportunity for exercise in Europe may have prevented variability in exercise activity from significantly affecting the passage of time.…”
Section: Discussionsupporting
confidence: 93%
“…The temporal distortion induced by physical activity is in line with previous reports ( Lambourne, 2012 ; Schwarz et al, 2013 ; Dormal et al, 2018 ; Behm and Carter, 2020 ; Petrizzo et al, 2022 ). However, in the study by Dormal et al (2018) , the authors conclude that the temporal distortion is not strictly related to physical activity per se but linked to other uncontrolled attentional or mnestic factors.…”
Section: Discussionsupporting
confidence: 92%
“…These common neural substrates suggest that physical exercise might affect time perception. A few studies reported that physical exercise could affect temporal judgments, inducing an overestimation of time intervals ( Lambourne, 2012 ; Duncan et al, 2016 ; Behm and Carter, 2020 ; Petrizzo et al, 2022 ). For example, Petrizzo et al (2022) performed a temporal and a numerosity discrimination task in which participants, while running, had to estimate whether the presented stimulus was the same or different from a memorized reference (600 ms interval or 24 dots).…”
Section: Introductionmentioning
confidence: 99%
“…Shivering patterns are variable among individuals, making the detection of shivering onset difficult to be determined objectively 48,49 . Moreover, exercise has been reported to increase cold tolerance 50 , and could therefore alter the detection of shivering onset during post-intervention personalized cold exposure, introducing a bias regarding the effect of exercise on BAT recruitment/activation. In the present work, however, the shivering threshold (assessed via the cooling vest water temperature at the onset of shivering [see Methods]) was not modified in any of the groups after the intervention (P = 0.154, Supplementary Table S1).…”
Section: Study Participantsmentioning
confidence: 99%